2014
DOI: 10.2146/ajhp130638
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate and dexmethylphenidate formulations for children with attention-deficit/hyperactivity disorder

Abstract: Abstract:Purpose: To review the current literature on the various extended-release methylphenidate stimulant preparations regarding safety and efficacy in children and adolescents with attentiondeficit/hyperactivity disorder (ADHD). Conclusions: Extended-release methylphenidate is effective in treating the symptoms of ADHD in children and adolescents. The different available dosage forms gives the clinician the opportunity to individualize treatment based on patient needs. * Data Sources: The literature includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…In the open-label, dose-optimization period, the most commonly reported TEAEs were consistent with those observed in children taking other MPH ER formulations for ADHD: decreased appetite, headache, abdominal pain, mood swings, irritability, and insomnia were among the most common AEs reported during the open-label, dose-optimization period of similarly designed studies of MPH ER capsule (Wigal et al 2014 ) and MPH ER oral suspension formulations (Robb et al 2014 ). AEs associated with MPH treatment generally occur early in treatment (Wolraich et al 2007 ; Sugrue et al 2014 ), and in the current study, fewer TEAEs were reported during the double-blind period, with similar percentages of subjects in the MPH ERCT and placebo groups reporting any AE. The most common TEAE reported during the double-blind period was URTI, reported by three subjects in each treatment group.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In the open-label, dose-optimization period, the most commonly reported TEAEs were consistent with those observed in children taking other MPH ER formulations for ADHD: decreased appetite, headache, abdominal pain, mood swings, irritability, and insomnia were among the most common AEs reported during the open-label, dose-optimization period of similarly designed studies of MPH ER capsule (Wigal et al 2014 ) and MPH ER oral suspension formulations (Robb et al 2014 ). AEs associated with MPH treatment generally occur early in treatment (Wolraich et al 2007 ; Sugrue et al 2014 ), and in the current study, fewer TEAEs were reported during the double-blind period, with similar percentages of subjects in the MPH ERCT and placebo groups reporting any AE. The most common TEAE reported during the double-blind period was URTI, reported by three subjects in each treatment group.…”
Section: Discussionsupporting
confidence: 65%
“…MPH was initially formulated as an immediate-release (IR) tablet requiring multiple daily doses for optimal treatment. Extended-release (ER) MPH formulations were later developed to provide all-day coverage, with the goal of eliminating the need for in-school administration, and to potentially increase efficacy and reduce adverse events (AEs) (Sugrue et al 2014 ). Several long-acting MPH formulations are currently available, including oral capsules and tablets (Concerta package insert 2015 ; Metadate CD package insert 2015 ; Ritalin LA package insert 2015), an oral suspension (Quillivant XR package insert 2016 ), and the transdermal patch (Daytrana package insert 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological treatment is considered effective and safe both for children and adults, but there is considerable inter-individual variability among patients regarding response to medication, required doses, and adverse events. Pharmacotherapy with methylphenidate (MPH) seems to be the first-line treatment of choice both in children 10, 11 and in adults 12, 13, 14, 15 with ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…Methylphenidate half‐life is approx. 3 h in children and adolescents . The study was conducted in accordance with the Declaration of Helsinki and had been approved by the local Ethics committee.…”
Section: Methodsmentioning
confidence: 99%